The effect of arc current on the corrosion behaviour of coated NiTi alloy on AISI304 by plasma transferred arc process - Dikici, B.; Ozel, S.; Gavgali, M.; Somunkiran, I. (Maik Nauka/Interperiodica/Springer, 2012)
In this study, the effect of arc current on the corrosion behaviour of NiTi coating on stainless steel has been investigated. NiTi powder mixture was alloyed on surface austenitic AISI304 by using plasma transferred arc (PTA) method. Surface alloying process is turned out using 80, 90, 100 A current densities and Ar atmosphere which is plasma and protective. The corrosion resistance of the coatings was analyzed by measuring the potentiodynamic polarization scanning (PDS) technique. Results indicate that corrosion resistances of the coatings decrease with increasing the arc current. In addition, the localized corrosion on the surface of produced coating at 100A is more activated than other coatings and the most passive coating in view of corrosion was obtained at produced coating at 80A.
Keywords: Cavitation Erosion Resistance; Shape-Memory Alloy; Stainless-Steel; Surface-Treatment; Coatings; 304-Stainless-Steel